SOCIO-ECONOMIC CONSEQUENCES OF DIGITAL DEVELOPMENT OF THE ECONOMY - Valentinovna Ogloblina, Elizaveta; Igorevna Seredina, Maria; Olegovna Altunina, Julia; Aleksandrovich Kodolov, Vladimir; Anatol'evich Lebedev, Kostyantyn (Revista Inclusiones, 2020)
The article deals with the analysis of the socio-economic implications of the digital economy development. It is established that by means of an interactive system of electronic communications, virtual companies, network communities, and business networks are formed creating an economic space without borders, which contributes to new forms of getting added value and digital dividends. It is revealed that considerable data generated as a result of economic modernization along with technologies for their analysis become one of the major assets of the state, business, and civil society. The authors prove that the absence of physical borders in the digital space opens access to a significant array of data for many participants in the global economic space. The article determines that the scientific justification of macroeconomic processes in interrelation with the development of the basic component of the digital economy –the digital communications industry – is important for the effective development of the digital economy institutions.